Publishing in Hematology Journals: A Scientometric and Economic Evaluation - (:unkn) unknown (CUREUS INC, 2020)
Introduction: Herein, we aimed to compare the scientometric data of hematology journals, and compare the publication models, especially the scientometric data of journals with all-open access (OA) and hybrid-OA publication models. Methods: Data were obtained from Scimago Journal & Country Rank and Clarivate Analytics InCites websites. Fifty-four journals indexed in Science Citation Index (SCI) and SCI-Expanded were evaluated. Bibliometric data and impact factor (IF), scientific journal rank (SJR), eigenfactor score (ES), and Hirsch (h)-index of the journals were obtained. United States dollar (USD) was used as the requested article publishing charge (APC). Statistics Package for the Social Sciences (SPSS, IBM Corp., Armonk, NY) version 23.0 was used for data analysis. Results: As a publication model, Hybrid-OA was the most common. One journal had subscription-only, and two journals had a free-OA model. Nine journals had a mandatory OA with the APC model and 42 journals used a hybrid model. The Median OA fee was 3400 USD. Hybrid-OA journals had a significantly higher median h-index (72 vs. 40, p=0.03) compared to all-OA journals. Other scientometric indexes were similar. When APCs were compared, all-OA journals were median 900 USD lower than hybrid-OA journals (2490 vs. 3400 USD, p=0.019). Conclusion: There is a widespread use of the OA publication model in hematology journals. Although hybrid OA journals have higher h-index, other scientometric indexes are similar. All-OA journals are more economically feasible considering a lower median APC. Further scientometric studies for journals in the field of hematology, randomized to follow citation per publication according to the OA model would better shed light on the data in this area.
Keywords: hematology; health scientometrics; scientometrics; open access publishing; economics; open access; EIGENFACTOR SCORE; RANK INDICATOR; IMPACT FACTOR; PUBLICATION FEES